2019
DOI: 10.1039/c9cp03798e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation studies of the structure and antifouling performance of a gradient polyamide membrane

Abstract: The structure and the antifouling performance of the first gradient polyamide layer model are systematically disclosed using molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…In contrast, molecular dynamics (MD) simulations can provide an atomic-scale understanding of the PA structure and water transport in the PA. In recent years, abundant equilibrium or nonequilibrium molecular dynamics (EMD and NEMD) simulations have been utilized to illustrate the formation of PA, and the structural characteristics of PA, and also water and ions or solutes transport in the PA, so as to potentially reveal the relationship between the structure and properties of PA membranes. Wei et al developed an efficient simulation method to construct the PA model with the highly cross-linked structure by dynamic polymerization, followed by the amplification and recross-linking steps .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, molecular dynamics (MD) simulations can provide an atomic-scale understanding of the PA structure and water transport in the PA. In recent years, abundant equilibrium or nonequilibrium molecular dynamics (EMD and NEMD) simulations have been utilized to illustrate the formation of PA, and the structural characteristics of PA, and also water and ions or solutes transport in the PA, so as to potentially reveal the relationship between the structure and properties of PA membranes. Wei et al developed an efficient simulation method to construct the PA model with the highly cross-linked structure by dynamic polymerization, followed by the amplification and recross-linking steps .…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al developed an efficient simulation method to construct the PA model with the highly cross-linked structure by dynamic polymerization, followed by the amplification and recross-linking steps . Li et al reported a novel tool for constructing PA membranes automatically through reactions between the functional groups on the monomers and constructed a gradient polyamide membrane model creatively . The microstructure of the PA membrane was described as the polymer chain structure and the cavity structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AIMD simulations are extremely costly and limited to studies of truncated systems (100–1000 atoms) for picosecond-scale phenomena, such as proton transport though bulk water . Albeit less accurate than ab initio molecular simulations, AAMD modeling has been demonstrated as a powerful tool for studying transport phenomena of water molecules and ions in nanoporous membranes. , AAMD simulations are spatiotemporally limited to nanoseconds and nanometers, whereas many transport phenomena occur on time scales larger than nanoseconds (e.g., transmembrane diffusion of ions down a concentration gradient occurs over milliseconds). To overcome this challenge, a group of atoms (e.g., a residue in a polymer) from all-atom models can be mapped into a single bead (an interaction site).…”
Section: Simulation Methods Across Various Scalesmentioning
confidence: 99%
“…To date, several limitations have prevented the widespread application of molecular simulations for water and ion transport in polymeric materials. , Unlike nonpolymeric nanochannels and membranes with well-defined nanostructures (e.g., carbon nanotubes , and graphene oxide , ), polymeric membranes have a complex structure and network of pores, which are very difficult to model. Existing simulation models of polymeric membranes, , although very valuable, may lack structural and chemical accuracy. The simulated polymerization relies on a simple heuristic criterion, where a new bond is introduced when the intermolecule distance between polymer chains is within a predefined distance.…”
Section: Introductionmentioning
confidence: 99%